The Decline of the Hegemonic Power of the United States and the Emergence of Multipolarism: Challenges for Latin America - Estenssoro-Saavedra, J (FLACSO-ECUADOR, 2023)
This paper exposes the debate about the decline of the hegemonic power of the United States in the world order, associated with the emergence of a new multipolar order. It is related to the debate on the validity of the North-South division after the end of the Cold War, to make a reflection concerning the complexities that Latin America could face, in a new multipolar order. The methodology is the historical analysis based on a review of primary and secondary sources. The stages of a debate that began in the eighties of the last century and that continues to the present are diachronically exposed. It concludes that regional unity is important to face the challenges of the emerging new world order.